Redesain Terminal Bandar Udara Tuanku Tambusai Dengan Pendekatan Arsitektur Neo Vernakular - Wulandari, Annisa Rizki; Firzal, Yohannes; Faisal, Gun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Tuanku Tambusai Airport as one of pioneer airport is located in Rokan Hulu, Riau. The planning to open for commercial flights and more routes has became a serious issues in order to redesigning and development of the airport. In this matter, in term of function and physical appearance of the airport’s terminal is one of important matter. In this regard, the research methods used conducted to collect field data, literatures, and empirical studies. This redesign attempt has expressing more local design senses and keeping up with the times. The result confirms that the principles of neo vernacular architecture can be more appropriated in expressing the local senses.Keyword: Neo Vernacular Architecture, Redesign, Terminal